Rheological properties of peanut protein isolate aggregation suspension and acid-induced gel - Huang, Zhigang; Wang, Xueying; Chi, Shangyi; Hua, Zhe; Bi, Chonghao (International Journal of Agricultural and Biological Engineering, 2021)
The dynamic rheological properties of peanut protein isolate (PPI) suspension and acid-induced PPI gels were studied. In frequency sweep test, the storage modulus (G′) and the loss modulus (G″) of PPI aggregation suspensions at different concentrations increased with the increase of frequency. The steady state shear flow test showed that PPI aggregation suspension had a thinning behavior of the shear, and the image of steady shear curve fitted the Carreau model. After gel formation, acid-induced PPI gels showed a typical Type I behavior (strain thinning) in strain sweep test, meaning that PPI gel got easily broken down, and there was a very small opportunity for the protein molecules to re-establish the network. Compared with the strain sweep of PPI aggregation suspensions and gels, the range of the storage modulus existed a dramatic difference, which could get about tenfold. As the frequency increased, both elasticity and viscosity increased in frequency sweep test, which indicated that the frequency dependence of the storage modulus increased with the increase of concentration. Keywords: peanut protein isolate (PPI), aggregation suspension, acid-induced PPI gel, dynamic rheological properties DOI: 10.25165/j.ijabe.20211403.6021 Citation: Huang Z G, Wang X Y, Chi S Y, Hua Z, Bi C H. Rheological properties of peanut protein isolate aggregation suspension and acid-induced gel. Int J Agric & Biol Eng, 2021; 14(3): 255–260.